G472 The pathway to diagnosis of type 1 diabetes in children: analysis of free text responses from a questionnaire study. (27th April 2015) - Zhu, H; Walter, F; Thompson, M; Usher-Smith, J
Abstract : Aims: Distinguishing the rare child presenting with new onset type 1 diabetes (T1D) from the large number with similar symptoms and minor undifferentiated illness is challenging for both primary care physicians and families. This study analyses free text responses from a questionnaire completed by parents of children recently diagnosed with T1D to explore the parents' perspectives of the pathway to diagnosis of T1D in children. Methods: A questionnaire about the pathway from first symptom (s) to diagnosis was completed by the parent (s)/guardian (s) of children aged 1 month to 16 years diagnosed with T1D within the previous three months in the East of England. The free text questions asked what they felt symptoms were due to, what factors contributed to their decision to seek medical advice and whether they felt there was anything that delayed reaching the diagnosis. Responses were grouped into similar categories and coded. Results: 88/164 (54%) of invited families returned the questionnaire. The time from symptom onset to diagnosis ranged from 2 to 315 days (median 25 days). Most of this was the appraisal interval from symptom onset until perceiving the need to seek medical advice (median 25 days (interquartile range 14–50)). Most parents found alternative explanations for their child's symptoms (Table 1 ). For example, polydipsia was attributed most commonly to hot weather (19/58, 33%) or infection (13/58, 22%), polyuria and nocturia were frequently explained by drinking more (29/47, 62% and 26/40, 65%) and tiredness was thought to be school related (12/44, 27%) or secondary to infection (5/44, 12%) or nocturia (4/44, 10%). Worsening or persistent symptoms was the most common reason parents mentioned for seeking medical help (n = 20) and their main concern at presentation was most commonly polydipsia (n = 40), followed by polyuria (n = 24). Finding alternative explanations for symptoms (n = 24) was the most common reason cited by parents for prolonging the time before diagnosis. Conclusions: The appraisal interval for T1D is complex for parents. Most parents find reasonable alternative explanations for their child's symptoms, which contributes to the time to diagnosis. Future interventions should recognise these difficulties and will need to include more than just a list of symptoms.